Comparison of isotonic activation of cell volume regulation in rat peritoneal mesothelial cells and in kidney outer medullary collecting duct principal cells - Baturina, Galina S.; Katkova, Liubov E.; Schmitt, Claus P.; Solenov, Evgeniy I.; Zarogiannis, Sotirios G. (Biomolecules, 2021)
In disease states, mesothelial cells are exposed to variable osmotic conditions, with high osmotic stress exerted by peritoneal dialysis (PD) fluids. They contain unphysiologically high concentrations of glucose and result in major peritoneal membrane transformation and PD function loss. The effects of isotonic entry of urea and myo-inositol in hypertonic (380 mOsm/kg) medium on the cell volume of primary cultures of rat peritoneal mesothelial cells and rat kidney outer medullary collecting duct (OMCD) principal cells were studied. In hypertonic medium, rat peritoneal mesothelial cells activated a different mechanism of cell volume regulation in the presence of isotonic urea (100 mM) in comparison to rat kidney OMCD principal cells. In kidney OMCD cells inflow of urea into the shrunken cell results in restoration of cell volume. In the shrunken peritoneal mesothelial cells, isotonic urea inflow caused a small volume increase and activated regulatory volume decrease (RVD). Isotonic myo-inositol activated RVD in hypertonic medium in both cell types. Isotonic application of both osmolytes caused a sharp increase of intracellular calcium both in peritoneal mesothelial cells and in kidney OMCD principal cells. In conclusion, peritoneal mesothelial cells exhibit RVD mechanisms when challenged with myo-inositol and urea under hyperosmolar isotonic switch from mannitol through involvement of calcium-dependent control. Myo-inositol effects were identical with the ones in OMCD principal cells whereas urea effects in OMCD principal cells led to no RVD induction.
Gesehen am 20.01.2022